Effects of resveratrol on reducing spermatogenic dysfunction caused by high-intensity exercise - Yuping Guo; Anli Wang; Xinpeng Liu; Enzhong Li (BMC, 2019)
Abstract Background Long-term high-intensity exercise can lead to reproductive endocrine and spermatogenic dysfunction. This research is to investigate the effect of resveratrol on the reduction of reproductive dysfunction induced by high-intensity exercise, and to screen relevant factors and signal transduction pathways. Methods Rats were randomly divided into three groups, a control group, an intensive exercise group (IE group), and a resveratrol-treated group (RSV group). After 9 weeks of exercise, the sperm density and reproductive hormone concentrations were measured, along with antioxidation, inflammatory cytokine production, and histological analyses performed for each group. In addition, a proteomics analysis of the IE group and RSV group were conducted. Results We found that compared with the control group, the average sperm density (P < 0.05) and testosterone concentration (P < 0.05) in the IE group decreased significantly. Additionally, in testis tissue the concentration of the inflammatory cytokines IL-6 (P < 0.01) and TNF-α (P < 0.01) increased significantly. Also, a significant decrease in superoxide dismutase (SOD) activity (P < 0.01) and a significant increase in the malondialdehyde (MDA) concentration (P < 0.01) were noted. In the RSV group, the average sperm density (P < 0.01), testosterone (P < 0.01) and follicle stimulating hormone (FSH) levels (P < 0.01) all increased in comparison to the IE group, and the concentration of IL-6 (P < 0.01) and TNF-α (P < 0.01) were found to be significantly decreased. Compared with the IE group, the SOD activity in the RSV group was significantly increased (P < 0.01), while the MDA content decreased (P < 0.01). Furthermore, histological analysis showed that the number of spermatogenic epithelial cells in the RSV group was higher than that of the IE group. There were a number of spermatogenic regulatory proteins identified in the proteomics analysis, including Clusterin, Piwi like homolog 1 (Piwil1), Zona pellucida binding protein (Zpbp), Heat shock-related 70 kDa protein 2 (Hspa2), Centrin 1, and Bardet-Biedl syndrome 2 protein (Bbs2). It was found that the proteins that differed between the two groups were mainly involved in pathways such as complement and coagulation cascades, the extracellular matrix-receptor interactions, etc. Conclusions The present study demonstrates that after high-intensity exercise, the inflammatory cascade in the tissue of the testis increases with decreased resistance to oxidation and disordered spermatogenic function. Resveratrol can improve the reproductive dysfunction of rats that was induced by high-intensity exercise. It mostly promotes reproductive function by increasing testosterone secretion, reducing the inflammatory response, improving the antioxidant capacity, affecting the expression of spermatogenic regulatory proteins, and enhancing the signal transduction pathway of spermatogenesis.